4
$\begingroup$

This problem arises from trying to solve, by Fourier transform, the Cauchy problem

$$\begin{cases} u_{tt}-u_{xxxx}=0 &x\in\mathbb{R},\, t\geq 0\\ \begin{cases} u(0,x)=f(x)\\ u_t(0,x)=0 \end{cases} \end{cases}$$

That is fourth-order wave PDE.

Doing formal integrals, I arrive at this expression after completing squares and using definitions of error functions:

$$\frac{1}{\sqrt{2\pi}}\int_{-\infty}^{\infty}\cosh(k^2t)e^{ikx}~dk=\frac{1}{4\sqrt{2t}}e^{-\frac{x^2}{4t}}\left[\text{erf}\left(\sqrt{t}\left(k-\frac{ix}{2t}\right)\right)+e^{\frac{x^2}{2t}}\text{erfi}\left(\sqrt{t}\left(k+\frac{ix}{2t}\right)\right)\right]_{-\infty}^{\infty}=\frac{1}{4\sqrt{2t}}e^{-\frac{x^2}{4t}}\biggl (2+e^{\frac{x^2}{2t}}\left[\text{erfi}\left(\sqrt{t}\left(k+\frac{ix}{2t}\right)\right)\right]_{-\infty}^{\infty}\biggr)$$

where I have evaluated $\text{erf}$ in the last line. My problem is that I know that $\text{erfi}$ does not have a limit when $k\to\infty$ since it is non-bounded over real line. However doing this inverse Fourier transform using corresponding Mathematica command gives me:

$$\frac{1}{\sqrt{2\pi}}\int_{-\infty}^{\infty}\cosh(k^2t)e^{ikx}~dk=\frac{1}{4\sqrt{2t}}e^{-\frac{x^2}{4t}}\left(2+2ie^{\frac{x^2}{2t}}\right)$$

where I have arranged the terms in order to get the same form as the result I have described before.

What am I not understanding?

$\endgroup$
  • 1
    $\begingroup$ Mathematica should be wrong in this case - in fact it is clear that the integral doesn't even converge. $\endgroup$ – user27126 Nov 14 '12 at 0:51
0
$\begingroup$

That means this Cauchy problem no longer can be solved by Fourier transform.

So you should use separation of variables:

Let $u(t,x)=T(t)X(x)$ ,

Then $T''(t)X(x)-T(t)X''''(x)=0$

$T''(t)X(x)=T(t)X''''(x)$

$\dfrac{T''(t)}{T(t)}=\dfrac{X''''(x)}{X(x)}=s^4$

$\begin{cases}T''(t)-s^4T(t)=0\\X''''(x)-s^4X(x)=0\end{cases}$

$\begin{cases}T(t)=\begin{cases}c_1(s)\sinh ts^2+c_2(s)\cosh ts^2&\text{when}~s\neq0\\c_1t+c_2&\text{when}~s=0\end{cases}\\X(x)=\begin{cases}c_3(s)\sinh xs+c_4(s)\cosh xs+c_5(s)\sin xs+c_6(s)\cos xs&\text{when}~s\neq0\\c_3x^3+c_4x^2+c_5x+c_6&\text{when}~s=0\end{cases}\end{cases}$

$\therefore u(t,x)=\int_0^\infty C_1(s)\sinh ts^2\sinh xs~ds+\int_0^\infty C_2(s)\sinh ts^2\cosh xs~ds+\int_0^\infty C_3(s)\sinh ts^2\sin xs~ds+\int_0^\infty C_4(s)\sinh ts^2\cos xs~ds+\int_0^\infty C_5(s)\cosh ts^2\sinh xs~ds+\int_0^\infty C_6(s)\cosh ts^2\cosh xs~ds+\int_0^\infty C_7(s)\cosh ts^2\sin xs~ds+\int_0^\infty C_8(s)\cosh ts^2\cos xs~ds$

$u_t(t,x)=\int_0^\infty s^2C_1(s)\cosh ts^2\sinh xs~ds+\int_0^\infty s^2C_2(s)\cosh ts^2\cosh xs~ds+\int_0^\infty s^2C_3(s)\cosh ts^2\sin xs~ds+\int_0^\infty s^2C_4(s)\cosh ts^2\cos xs~ds+\int_0^\infty s^2C_5(s)\sinh ts^2\sinh xs~ds+\int_0^\infty s^2C_6(s)\sinh ts^2\cosh xs~ds+\int_0^\infty s^2C_7(s)\sinh ts^2\sin xs~ds+\int_0^\infty s^2C_8(s)\sinh ts^2\cos xs~ds$

$u_t(0,x)=0$ :

$\int_0^\infty s^2C_1(s)\sinh xs~ds+\int_0^\infty s^2C_2(s)\cosh xs~ds+\int_0^\infty s^2C_3(s)\sin xs~ds+\int_0^\infty s^2C_4(s)\cos xs~ds=0$

$\int_0^\infty s^2C_3(s)\sin xs~ds=-\int_0^\infty s^2C_1(s)\sinh xs~ds-\int_0^\infty s^2C_2(s)\cosh xs~ds-\int_0^\infty s^2C_4(s)\cos xs~ds$

$\mathcal{F}_{s,s\to x}\{s^2C_3(s)\}=-\int_0^\infty s^2C_1(s)\sinh xs~ds-\int_0^\infty s^2C_2(s)\cosh xs~ds-\mathcal{F}_{c,s\to x}\{s^2C_4(s)\}$

$C_3(s)=-\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty s^2C_1(s)\sinh xs~ds\}}{s^2}-\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty s^2C_2(s)\cosh xs~ds\}}{s^2}-\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\mathcal{F}_{c,s\to x}\{s^2C_4(s)\}\}}{s^2}$

$\therefore u(t,x)=\int_0^\infty C_1(s)\sinh ts^2\sinh xs~ds+\int_0^\infty C_2(s)\sinh ts^2\cosh xs~ds+\int_0^\infty C_4(s)\sinh ts^2\cos xs~ds-\int_0^\infty\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty s^2C_1(s)\sinh xs~ds\}\sinh ts^2\sin xs}{s^2}ds-\int_0^\infty\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty s^2C_2(s)\cosh xs~ds\}\sinh ts^2\sin xs}{s^2}ds-\int_0^\infty\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\mathcal{F}_{c,s\to x}\{s^2C_4(s)\}\}\sinh ts^2\sin xs}{s^2}ds+\int_0^\infty C_5(s)\cosh ts^2\sinh xs~ds+\int_0^\infty C_6(s)\cosh ts^2\cosh xs~ds+\int_0^\infty C_7(s)\cosh ts^2\sin xs~ds+\int_0^\infty C_8(s)\cosh ts^2\cos xs~ds$

$u(0,x)=f(x)$ :

$\int_0^\infty C_5(s)\sinh xs~ds+\int_0^\infty C_6(s)\cosh xs~ds+\int_0^\infty C_7(s)\sin xs~ds+\int_0^\infty C_8(s)\cos xs~ds=f(x)$

$\int_0^\infty C_7(s)\sin xs~ds=f(x)-\int_0^\infty C_5(s)\sinh xs~ds-\int_0^\infty C_6(s)\cosh xs~ds-\int_0^\infty C_8(s)\cos xs~ds$

$\mathcal{F}_{s,s\to x}\{C_7(s)\}=f(x)-\int_0^\infty C_5(s)\sinh xs~ds-\int_0^\infty C_6(s)\cosh xs~ds-\mathcal{F}_{c,s\to x}\{C_8(s)\}$

$C_7(s)=\mathcal{F}^{-1}_{s,x\to s}\{f(x)\}-\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty C_5(s)\sinh xs~ds\}-\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty C_6(s)\cosh xs~ds\}-\mathcal{F}^{-1}_{s,x\to s}\{\mathcal{F}_{c,s\to x}\{C_8(s)\}\}$

$\therefore u(t,x)=\int_0^\infty C_1(s)\sinh ts^2\sinh xs~ds+\int_0^\infty C_2(s)\sinh ts^2\cosh xs~ds+\int_0^\infty C_4(s)\sinh ts^2\cos xs~ds-\int_0^\infty\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty s^2C_1(s)\sinh xs~ds\}\sinh ts^2\sin xs}{s^2}ds-\int_0^\infty\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty s^2C_2(s)\cosh xs~ds\}\sinh ts^2\sin xs}{s^2}ds-\int_0^\infty\dfrac{\mathcal{F}^{-1}_{s,x\to s}\{\mathcal{F}_{c,s\to x}\{s^2C_4(s)\}\}\sinh ts^2\sin xs}{s^2}ds+\int_0^\infty C_5(s)\cosh ts^2\sinh xs~ds+\int_0^\infty C_6(s)\cosh ts^2\cosh xs~ds+\int_0^\infty C_8(s)\cosh ts^2\cos xs~ds+\int_0^\infty\mathcal{F}^{-1}_{s,x\to s}\{f(x)\}\cosh ts^2\sin xs~ds-\int_0^\infty\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty C_5(s)\sinh xs~ds\}\cosh ts^2\sin xs~ds-\int_0^\infty\mathcal{F}^{-1}_{s,x\to s}\{\int_0^\infty C_6(s)\cosh xs~ds\}\cosh ts^2\sin xs~ds-\int_0^\infty\mathcal{F}^{-1}_{s,x\to s}\{\mathcal{F}_{c,s\to x}\{C_8(s)\}\}\cosh ts^2\sin xs~ds$

$\endgroup$
  • 3
    $\begingroup$ I have no idea what's going on, but wow that's a lot of LaTeX. $\endgroup$ – Javier Nov 18 '12 at 1:31
  • 2
    $\begingroup$ Well, I don't know what are you saying since Fourier transform is "separation of variables made continuous". However your separation of variables has a lot of integrals that, as the one I propose, doesn't converge at all. And I note that you doesn't take into account that the domain of integration must be $\mathbb{R}$ since we can't suppose parity. $\endgroup$ – elessartelkontar Nov 19 '12 at 20:30
1
$\begingroup$

It must be an error, because this Fourier integral doesn't even converge as tempered distributions, let alone as functions.

In general, anything of exponential growth or more doesn't have a Fourier transform in any sense.

$\endgroup$
  • $\begingroup$ For many purposes, it is true that functions of exponential growth (and general not-necessarily-tempered distributions) "do not have Fourier transforms", ... in the sense that they do not have Fourier transforms that are tempered distributions or non-tempered distributions. But, since we know that FT maps distributions isomorphically to the Paley-Wiener space, FT maps general distributions (isomorphically!) to the dual of the Paley-Wiener space. Ok,... but often this true fact is not useful... But it is always a possibility... $\endgroup$ – paul garrett Mar 13 '18 at 20:41

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.